Характеристика психосоматичного статусу жінок з ендопротезованим кульшовим суглобом у післяпологовому періоді його корекції засобами фізичної терапії - Данильченко, С. І.; Канигіна, Світлана Миколаївна; Danylchenko, S. I.; Kanyhina, S. М. (My University, 2023)
Метою дослідження була оцінка ефективності розробленої програми фізичної терапії за динамікою показників, що характеризують психосоматичний статус жінок з ендопротезованим кульшовим суглобом, які перенесли кесарів розтин. Контрольну групу склали 19 жінок без ендопротезів суглобів нижніх кінцівок. Основну групу склали 9 жінок через 1 місяць після пологів, які відбулись шляхом кесаревого розтину. Розроблена програма фізичної терапії тривала 1 місяць. Були застосовані терапевтичні вправи; функціональне тренування, proprioceptive neuromuscular facilitation; масаж нижніх кінцівок, спини. Були враховані рухові обмеження, пов’язані з неповністю сформованим рубцем після кесаревого розтину, та з наявністю ендопротеза; відповідно були створені безпечні стратегії рухів, пов’язаних з доглядом за дитиною. Були визначені показники фізичного (кистьова та станова динамометрія, проба PWC170) та психоемоційного (Единбурзька шкала післяпологової депресії, ЕШПД) статусу. При первинному обстеженні у жінок з ендопротезованим кульшовим суглобом виявлено погіршення психосоматичного статуту – м’язову слабкість (за результатами динамометрії), низьку фізичну працездатність (за PWC170), психоемоційне пригнічення (за ЕШПД). Покращення результату станової динамометрії та індексу станової сили при повторному обстеженні в контрольній групі становило відповідно 14,7 % та 9,9 %, в основній групі – 27,2 % та 21,7 %. Сила китиці не змінилась в обох групах жінок порівняно з первинним обстеженням. Фізична працездатність за результатами PWC170 у жінок контрольної групи покращилась на 13,45 %, основної групи – 41,5 %. У контрольній групі покращення психоемоційного статусу за ЕШПД в контрольній групі становило 32,9 %, в основній групі – 38,8 %. За результатами дослідження був зроблений висновок, що засоби фізичної терапії доцільно призначати у комплексному відновленні жінок з ендопротезованим кульшовим суглобом, які перенесли кесарів розтин, для зменшення м’язової слабкості, збільшення працездатності, покращення психоемоційного статусу. The purpose of the study was to evaluate the effectiveness of the developed physical therapy program based on the dynamics of indicators characterizing the psychosomatic status of women with an endoprosthetic hip joint who underwent cesarean section. The control group consisted of 19 women without endoprostheses of the joints of the lower limbs. The main group consisted of 9 women 1 month after childbirth, which took place by caesarean section. The developed program of physical therapy lasted 1 month. Therapeutic exercises were applied; functional training, proprioceptive neuromuscular facilitation; massage of lower limbs, back. Movement limitations associated with an incompletely formed scar after cesarean section and the presence of an endoprosthesis were taken into account; accordingly, safe strategies for movements related to child care were created. Indicators of physical (hand and standing dynamometry, PWC170) and psychoemotional (Edinburgh Postnatal Depression Scale) status were determined. During the initial examination, deterioration of the psychosomatic status was found in women with an endoprosthetic hip joint – muscle weakness (according to dynamometry), low physical capacity (according to PWC170), psycho-emotional depression (according to the Edinburgh Postnatal Depression Scale). During re-examination, the condition of women characterized the dynamics of physiological recovery after abdominal delivery and the effectiveness of the physical therapy program in women of the main group. The improvement in static dynamometry and static strength index in the control group was 14.7% and 9.9%, respectively, in the main group – 27.2% and 21.7%. According to the results of PWC170, the physical performance of women in the control group improved by 13.4 %, and in the main group by 41.5%. In the control group, the improvement of psychoemotional status according to the Edinburgh Postnatal Depression Scale in the control group was 32.9 %, in the main group – 38.8 %. Based on the results of the study, it was concluded that it is advisable to prescribe physical therapy in the complex recovery of women with an endoprosthetic hip joint who underwent cesarean section, to reduce muscle weakness, increase work capacity, and improve psycho-emotional status.
Characterization of the psychosomatic status of women with an endoprosthetic hip joint in the postpartum period and the effectiveness of its correction by means of physical therapy
Keywords: реабілітація; абдомінальне пологорозрішення; ендопротез суглоба нижніх кінцівок; rehabilitation; abdominal delivery; lower extremity joint endoprosthesis